Oral health and rheumatoid arthritis: a case control study - Tamášová, Margaréta; Macejová, Želmíra; Dorko, Erik; Timková, Silvia; Rimárová, Kvetoslava; Diabelková, Jana (Central European journal of public health, 2024)
OBJECTIVES: Patients suffering from rheumatoid arthritis (RA) are repeatedly affected by oral diseases or problems, including dental caries and periodontal diseases (PDs). Periodontitis and rheumatoid arthritis are chronic inflammatory destructive diseases that share many similarities. The objective of this study was to assess oral health status including examination of hard dental tissues and periodontium in patients with rheumatoid arthritis and compare the results with healthy controls. We hypothesize some interlink between oral diseases and RA. METHODS: The epidemiological case-control study involved a total of 64 subjects divided into an experimental group (14 rheumatoid arthritis cases) and a control group (50 healthy individuals). Disease activity in the subjects with RA was assessed by the Disease Activity Score (DAS28). The number of Decayed, Missing and Filled Teeth (DMFT) and Community Periodontal Index of Treatment Need (CPITN) as a basic epidemiological oral health indexes were recorded. Finally, the data were analysed statistically. RESULTS: The RA patients (19.21, SD = 6.95) showed a higher caries index level measured by DMFT than the control group (17.72, SD = 6.19); the difference was not statistically significant (U = 387.5, p = 0.547). In terms of a mean number of teeth decayed (p = 0.078), teeth filled due to caries (p = 0.397), and missing teeth (p = 0.126), the two groups were not significantly different. In terms of periodontal health, a significant difference was observed between the two groups concerning the CPI maximum score (p = 0.003). The RA patients showed higher prevalence of periodontitis than the controls. CONCLUSIONS: A complete basic oral examination, along with an oral health instruction including adequate oral and dental hygiene, is crucial to prevent dental caries and periodontal diseases and associated complications in RA patients, since they appear to be more vulnerable than the non-RA population.
Keywords: Dental Caries; Oral Health; nemoci parodontu; Periodontal Diseases; Humans; Case-Control Studies; lidé středního věku; DMF Index; studie případů a kontrol; Arthritis, Rheumatoid; Female; Aged; dospělí; orální zdraví; senioři; lidé; revmatoidní artritida; Adult; zubní kaz; ženské pohlaví; Male; Middle Aged; mužské pohlaví